Racial/ethnic variation in the prevalence of vaccine-related human papillomavirus genotypes. Issue 7 (3rd October 2019) - Montealegre, Jane R.; Varier, Indu; Bracamontes, Christina G.; Dillon, Laura M.; Guillaud, Martial; Sikora, Andrew G.; Follen, Michele; Adler-Storthz, Karen; Scheurer, Michael E.
ABSTRACT: Objective: There are currently three licensed human papillomavirus (HPV) vaccines that protect against cervical cancer. Here we compare the prevalence of bi-, quadri-, and nonavalent vaccine-related HPV genotypes in a multi-ethnic sample of non-Hispanic white, non-Hispanic black, Hispanic, and Asian women. Design: Patients in this analysis ( n  = 419) represent a subset of women with a previous abnormal Pap test participating in a clinical trial. HPV genotyping was conducted using the Roche Linear Array. Prevalent HPV genotypes were grouped according to their inclusion in each of the vaccines: bivalent (16, 18), quadrivalent (16, 18, 6, 11), and nonavalent (16, 18, 31, 33, 45, 52, 58, 6, 11). Results: The prevalence of HPV genotypes covered by the bi-/quadrivalent vaccines was lowest among non-Hispanic black (15%) and Hispanic women (20%), compared to non-Hispanic white (38%) and Asian women (38%). Across all racial/ethnic groups, a large proportion of infections (38%–49%) were with genotypes included in the nonavalent vaccine. However, the prevalence of HPV genotypes not covered by any vaccine was significantly higher among non-Hispanic black (36%) and Hispanic women (42%), compared to non-Hispanic white (24%) and Asian women (16%) ( p  < 0.001). Racial/ethnic differences in HPV genotype prevalence were observed when controlling for demographic and sexual behavior characteristics, as well as when restricting the analysis to women with CIN 2+. Conclusion: Our data suggest racial/ethnic differences in the prevalence of vaccine-related HPV genotypes. In particular, non-Hispanic black and Hispanic women had the lowest prevalence of HPV genotypes covered by the bi-/quadrivalent vaccines. While a large proportion of their infections were covered by the nonavalent vaccine, non-Hispanic black and Hispanic women also had the highest prevalence of HPV genotypes not covered by any vaccine.